Evaluation of the Influence of pH on the Release of Exchangeable Cations from a Mixed Clay Mineral Deposit for Replenishment of Soil Nutrients - Irabor, Emmanuel Enoguan Ighodaro; Esanukpe, Linda; Imafidon, Monday Idiaghe; Ogbeide, Osahon Kennedy; Okunzuwa, Iyobosa Gift; Unuigbe, Charles Akhadelor; Omoruyi, Uwaila (Walisongo Journal of Chemistry, 2023)
Soil nutrients consist of minerals such as Ca, Mg, K and Na ions among others which are essential to plant growth. Soils can become deficient in these nutrients on account of pollution, flooding and over cultivation. The soil condition can be ameliorated by addition of clay minerals which are rich in aforementioned cations. The mineralogy of the clay mineral was investigated using X-ray Diffractometer (XRD) and the effect of pH variation on the release of exchangeable cations of the clay mineral deposit were investigated by varying the pH of the solution in which the clay mineral was immersed whereas the amount of the cations released were determined using Atomic Absorption Spectrophotometer(AAS) and Flame Emission Spectrophotometer.  Three clay minerals clinochlore, kaolinite and illite were detected. The quantity of cations released from the clay mineral varied with pH; and the pH at which the maximum quantity   of the cations were released were pH4 for K+ ions(4.63±0.38cmol/kg), pH7 Ca2+ (12.09±0.96 cmol/kg) and Mg2+(3.48±0.08 cmol/kg) ions and pH8 for Na+(7.81±0.58 cmol/kg) ions respectively for site 1. This trend was observed in the three sites that were studied. This study has revealed that different pH conditions are required if this mixed clay mineral is to be employed in the remediation of nutrient deficiency in any soil in respect of a particular mineral.